Characteristics of F0 Values and Organoleptic Canned Roa Chili Sauce with Different Sterilization Periods - Ransingin, Winarsih; Rasulu, Hamidin; Rodianawati, Indah (Universitas Khairun, 2025)
North Maluku is rich in marine biodiversity, including small pelagic fish such as julung-julung fish (Hemirhamphus sp.), which are often processed into sambal roa, a traditional chili sauce made from smoked fish and spices. This product is well known as a traditional food and regional souvenir, but traditional processing methods result in a short shelf life and vulnerability to microbial contamination. This study aims to determine the effect of sterilization duration on F₀ value, and organoleptic quality of canned sambal roa. The research was conducted using a completely randomized design (CRD) with four sterilization times at 121°C: 15, 20, 25, and 30 minutes. The results showed that F₀ values increased with longer sterilization times, reaching the highest value of 6.02 minutes in treatment P4 (30 minutes). Organoleptic tests revealed the highest scores in treatment P4 for color (7.88), taste (8.46), aroma (7.67), and texture (8.13), all of which were in the